Categorizing Risks and Success Factors of Water Industry in Malaysia - Tamam, Mohamad Hisyam Selamat, Amir Hamzah; Soon, Foo Kok; Selladurai, Sugumaran (Journal of Public Administration and Governance, 2022)
This study investigated categories of risks and success factors associated with water industry in Malaysia. Seven risk categories were proposed, which are technology, organization, economy, government, nature, crime and public. The proposed categories of success factors were regulatory agencies, water operators, financial, assets, human resource, contract and public. Categories of risks and success factors were developed based on the integration of theory of perceived risk (Bauer, 1960), risk items of Ameyaw (2015), stakeholder theory and legitimacy theory. To validate the proposed categories of risks and success factors, 100 questionnaires were distributed by post to the management personnel of water operators and 32 questionnaires were returned. Descriptive analysis and relative importance index were used to analyze the data. The results indicated highest agreement towards the occurrence of risk factors in term of technology, economy and public. However, there was a big gap between risks’ probability of occurrence and risk allocation and also between severity of risk factors and risk allocation amongst water operators in Malaysia. This highlights low awareness amongst water operators in Malaysia on water risk management. Additionally, the respondents considered all items of success factors as important. Implicit in these findings is that there is a need for the regulatory agencies to play an active role in promoting risk management awareness amongst water operators through campaign, workshop and training programs.